THE EFFECT OF FINANCIAL LITERATURE ON STUDENT BEHAVIOR IN MANAGING FINANCIAL FACULTY OF ECONOMICS AND BUSINESS UNIVERSITAS MUHAMMADIYAH SUMATRA UTARA - Yuyi Mahyuni Pohan; Julita Julita (Proceeding International Seminar of Islamic Studies, 2022)
The low level of financial literacy among students based on the OJK survey explained that most students still do not understand the concept of finance, even though students should be biased independently manage their finances well and are responsible for the financial satisfaction they make, because for them they manage their own finances without parentalsupervision. In accordance with the problems posed in the study, the purpose of this study aims to determine the level of financial literacy of Management Study Program Students, Faculty of Economics and Business, UMSU. To find out the effect of student financial litteration on the financial management of Management Study Program Students, Faculty of Economics and Business, UMSU. This research is a quantitative study with data collection techniques using questionnaires. The number of sampe used was 85 students of the management study program of the University of Muhammadiyah North Sumatra. Based on the t testobtained with a calculated T valueof 4.023 and a table T provision valueof 1.989 (4.023 1.989), and a significant value of 0.000 0.05 , Then H0 is rejected. What is important is the influence of financial literacy on the financial management of UMSU Faculty of Economics and Business students. Based on the value (R-Square) of 0.163 shows a variable financial literacy towards financial management of 16.3%, while the remaining 83.7% can be explained by other independent variabes that were not included in this study.